Transcriptomic Survey of the Midgut of Anthonomus grandis (Coleoptera: Curculionidae) - Salvador, Ricardo; Perez Principi, Ricardo Dario; Berretta, Marcelo Facundo; Fernandez, Paula Del Carmen; Paniego, Norma Beatriz; Sciocco, Alicia Ines; Hopp, Horacio Esteban (Entomological Society of America, 2019)
Anthonomus grandis Boheman is a key pest in cotton crops in the New World. Its larval stage develops within the flower bud using it as food and as protection against its predators. This behavior limits the effectiveness of its control using conventional insecticide applications and biocontrol techniques. In spite of its importance, little is known about its genome sequence and, more important, its specific expression in key organs like the midgut. Total mRNA isolated from larval midguts was used for pyrosequencing. Sequence reads were assembled and annotated to generate a unigene data set. In total, 400,000 reads from A. grandis midgut with an average length of 237 bp were assembled and combined into 20,915 contigs. The assembled reads fell into 6,621 genes models. BlastX search using the NCBI-NR database showed that 3,006 unigenes had significant matches to known sequences. Gene Ontology (GO) mapping analysis evidenced that A. grandis is able to transcripts coding for proteins involved in catalytic processing of macromolecules that allows its adaptation to very different feeding source scenarios. Furthermore, transcripts encoding for proteins involved in detoxification mechanisms such as p450 genes, glutathione-S-transferase, and carboxylesterases are also expressed. This is the first report of a transcriptomic study in A. grandis and the largest set of sequence data reported for this species. These data are valuable resources to expand the knowledge of this insect group and could be used in the design of new control strategies based in molecular information.